Axial and mean diffusivity predict myelin density in the hippocampus of pigs during early brain development, independent of sex - Sutkus, Loretta T.; Li, Zimu; Sommer, Kaitlyn M.; Dilger, Ryan N. (Frontiers in Neuroscience, 2025)
IntroductionIn the developmental field, sex differences can alter brain growth and development. Across the literature, sex differences have been reported in overall brain volume, white matter, gray matter and numerous other regions and tracts captured through non-invasive neuroimaging. Growing evidence suggests that sex differences appear at birth and continue through childhood. However, limited work has been completed in translational animal models, such as the domestic pig. Additionally, when using neuroimaging, uncertainties remain about which method best depicts microstructural changes, such as myelination.Materials and methodsTo address this gap, the present study utilized a total of 24 pigs (11 intact males or boars; 13 females or gilts) that underwent neuroimaging at postnatal day (PND) 29 or 30 to assess overall brain structural anatomy (MPRAGE), microstructural differences using diffusion (DTI), and an estimation of myelin content via myelin water fraction (MWF). On PND 32, brains were collected from all pigs, with the left hippocampus isolated, sectioned, and stained using the Gallyas silver impregnation method to quantify myelin density.ResultsMinimal sex differences were observed across neuroimaging modalities, with only myelin content exhibiting sex differences in the hippocampus (P = 0.022). In the left hippocampus (P = 0.038), females had a higher MWF value compared with males. This was supported by histologically derived myelin density as assessed by positive pixel percentage, but differences were isolated to one anatomical plane of the hippocampus (P = 0.024) and not the combined mean value (P = 0.333). Further regression analysis determined that axial (P = 0.01) and mean (P = 0.048) diffusivity measures, but not fractional anisotropy or MWF, were positively correlated with histologically derived myelin density in the left hippocampus, independent of sex.DiscussionThese findings suggest that at 4 weeks of age, axial and mean diffusivity may better reflect myelin density. Further investigation is required to confirm underlying mechanisms. Overall, minimal sex differences were observed in 4-week-old domestic pigs, indicating similar brain structure at this early stage of development.